Productivity and profitability of Indian mustard under different organic nutrient management practices in Semi-arid region - RK Sharma,; SK Sharma,; JK Balyan, (Journal of Oilseed Brassica, 2026)
A field experiment was conducted to study the effect of the different organic nutrient sources on productivityand profitability of Indian mustard [Brassica juncea (L.) Czern & Coss.]. Eight treatments having threeorganic sources viz., farmyard manure, vermicompost and poultry manure with or without biodynamic manure500 and 501 was laid out in a randomized block design replicated thrice. The organic source comprisingcombined application of poultry manure @ 1.7 t/ha along with biodynamic manure 500 + BD 501 producedsignificantly higher seed yield (1966 kg ha-1) and stover yield (5169 kg ha-1) to the tune of 78.7 and 52.4 percent higher over control, respectively. Growth and yield attributes viz., plant height (161.5 cm), number ofbranches per plant (5.2), length of siliqua (6.0 cm), number of siliqua per plant (235.6), number of seeds persiliqua (15.4) and test weight (5.1 gm) of mustard were significantly higher with poultry manure @ 1.7 t/ha +BD 500 + BD 501 over the no manure application and superior over rest organic treatments. Application ofpoultry manure @ 1.7 t/ha + BD 500 + BD 501 gave highest net return (Rs. 51204 ha-1) and B: C ratio (2.9).